Analysis of the Interpretations of Imam Al-Qurtubi and Muhammad Quraish Shihab on Verses about Riba and Their Implications for Financial Awareness - Sutardi, Edi; Ahmad, Khadher (UIN Sunan Gunung Djati Bandung, 2024)
This research analyzes Al-Qurtubi and Quraish Shihab regarding the riba verse and its implications for financial awareness. The instructions in the Qur'an are clear about the haram and the dangers of usury for humans. However, the reality on the ground is that there are still many people who fall into usury. So that his financial affairs have worldly problems and his spiritual blessings are lost. This research aims to understand the integral conception of usury through the interpretation of Al-Qurtubi and Quraish Shihab, their correlation or differentiation, and their implications. The authors collect verses related to usury and their interpretations, develop a theoretical basis, analyze the correlation and differentiation, and put forward the implications. This process uses comparative analysis by compromising the interpretation of the books Al-Qurtubi and Al-Misbah. The research uses a descriptive-analytical method with a qualitative model through literature study. The results of the research show that the verses of the Qur'an about usury are spread across four suras, namely Al-Baqarah[2]: 275-279, Ali-Imran[3]: 130-132, An-Nisa[4]: 160-161, and Ar-Rum[30]: 39. According to the two commentators, the law of usury is haram. The legal illat is the addition of debt due to deferrals and excesses in contracts or certain staple foods. Understanding this interpretation has positive implications for the financial awareness of believers who are true to their faith.